An empirical study on cost efficiency and loan loss provisioning behavior in Vietnamese banks - Pham, Tri Trung (2020)
This paper examines bank cost efficiency and loan loss provisioning behavior of 31 Vietnamese commercial banks during the period from 2012 to 2019. Beside the examination of three loan loss provisioning hypotheses, including income smoothing, capital management and business cycle, results of cost efficiency scores are utilized in analyzing the relationship between banks’ efficiency and loan loss provisioning practice. This paper evaluates banks’ efficiency levels from a translog cost function prior to incorporating the estimated cost efficiency into the Generalized Method of Moment estimator regression of loan loss provisioning behavior. The empirical results indicate that Vietnamese banks have an average efficiency score of 93.47%. The estimated results from the Generalized Method of Moment estimators provide evidence supporting the existence of income smoothing and capital management hypotheses, whereas no evidence for business cycle is found. Furthermore, cost efficiency significantly explains the behavior of loan loss provision practice among Vietnamese banks in a way that banks with greater level of cost efficiency demonstrate a lower level of loan loss provisions.